2012
DOI: 10.1371/journal.pone.0036748
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mhc and Neutral Variation in Peary Caribou: Genetic Drift Is Not Mitigated by Balancing Selection or Exacerbated by Mhc Allele Distributions

Abstract: Theory and empirical results suggest that the rate of loss of variation at Mhc and neutral microsatellite loci may differ because selection influences Mhc genes, and because a high proportion of rare alleles at Mhc loci may result in high rates of loss via drift. Most published studies compare Mhc and microsatellite variation in various contemporary populations to infer the effects of population size on genetic variation, even though different populations are likely to have different demographic histories that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 71 publications
(82 reference statements)
1
36
1
Order By: Relevance
“…; Taylor et al . ). When a population experiences a rapid decrease in size, the expected outcome is an immediate reduction in allelic richness, followed by loss of heterozygosity over time if the population remains small and isolated (Allendorf ; Frankham et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Taylor et al . ). When a population experiences a rapid decrease in size, the expected outcome is an immediate reduction in allelic richness, followed by loss of heterozygosity over time if the population remains small and isolated (Allendorf ; Frankham et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Taylor et al . ). Here, we assess the impacts of different bottleneck severities on MHC class II B (MHCIIB) and putatively neutral microsatellite variation by comparing genetic diversity during the early years of population declines (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…A recent meta-analysis of the roles of natural selection and genetic drift in shaping MHC variation concluded that selection combined with drift during population bottlenecks can result in loss of MHC polymorphism at even greater rates than neutral genetic diversity [93]. Other studies have shown that microsatellite and MHC diversity is lost in similar proportions over time, with balancing selection unable to mitigate genetic drift [94] and that MHC diversity declines more steeply than microsatellite diversity after a bottleneck [95]. However, inconsistencies remain and in some cases selection can maintain polymorphism at MHC loci during population bottlenecks (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…; Oliver & Piertney ; Taylor et al . ). In the current study, we take advantage of a complete and reliable pedigree that has been constructed for our study population based on breeding observations and offspring banded in the nest (Townsend & Jamieson ), as well as detailed data of the reproductive success of all breeders and genotypes of their offspring.…”
Section: Introductionmentioning
confidence: 97%